Effectiveness of Tikrar Method to Support Quran Memorization Ability of Students of Elementary School Muhammadiyah 04 Surabaya - Fauziyah, Jihan; Hidayat, Moch Charis; Puspitasari, Ika (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This research aims to describe the effectiveness of applying the Tikrar method in improving the ability to memorize the Al-Qur'an in grade 5 students at SD Muhammadiyah 04 Surabaya. The Tikrar method, which prioritizes repetition of verses from the Koran, has proven effective in speeding up and strengthening students' memory process. The research used a qualitative approach with case studies, involving interviews with school principals, tahfidz teachers, and direct observation of the student learning process. The research results showed that almost 90% of class 5A students succeeded in memorizing Juz 30 after applying the Tikrar method, which was supported by a conducive learning environment, such as a comfortable classroom atmosphere and intensive guidance from the tahfidz teacher. The main supporting factors for the success of this method are student motivation and the role of parents, although there are challenges in supporting at home. The Tikrar method has been proven to be more effective than the previously used talaqqi method, especially in terms of time efficiency and memorization quality. This research suggests integrating social media or digital-based learning applications to support rote repetition outside school hours.